The Influence of Reading Activities with Parents on Early Childhood Literacy Skills - Ibnu Imam Al Ayyubi; Siti Fatinnah binti Ab Rahman; Putri Puji Asiani Oktavia; Rismayanti Prilian; Risa Alfina Fadilah; Aziz Nurul Ilmi (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2025)
This study aims to explore how shared reading activities between parents and children are associated with early childhood literacy development. Employing a qualitative case study approach, the research was conducted at TK Wulil Amri over a three-month period. Participants consisted of six children, six parents, and two teachers who were directly involved in shared reading practices. Data were collected through in-depth interviews, participatory observations, and documentation, and were analyzed using thematic analysis through systematic coding and triangulation of data sources and methods. The findings reveal recurring patterns indicating that children who regularly engage in shared reading with their parents tend to demonstrate emerging literacy behaviors, including letter recognition, vocabulary expansion, early reading comprehension, and increased interest in books. In addition, shared reading activities appear to foster positive emotional interactions between parents and children, contributing to a supportive home literacy environment. These findings suggest that parent child shared reading may serve as an important supportive strategy in promoting early childhood literacy development when implemented consistently and interactively within the family context.